STUDI EMPIRIS RISK MANAGEMENT, SUSTAINABILITY REPORT DISCLOSURE, DAN DISCLOSURE ON THE WEBSITE TERHADAP NILAI PERUSAHAAN - Kesia Amelia (Ma Chung Press, 2016)
This study aims to identify the positive influence of risk management disclosures, sustainability report, and disclosure through the website of the company's value. The samples are manufacturing companies listed in Indonesia Stock Exchange 2010–2014. From the results of purposive sampling, acquired 118 companies that required in the criteria of 142 manufacturing companies exist. This study includes the design of quantitative research with non-experimental correlational approach, and using multiple linear regression analysis. This study has found that the risk management disclosures have a negative effect or no effect on firm value. This is due to the competitive cost disadvantage of the disclosure by the company. Another result of this study found that the disclosure of sustainability report and disclosure through the website have a positive effect on firm value. Both disclosures are proven to increase the credibility and success which characterized by a high value of the company, allowing the company to grow continuously (sustainable).